Association of Hemoglobin Glycation Index With Contrast-Induced Acute Kidney Injury in Patients Undergoing Coronary Angiography: A Retrospective Study - Chen, Zhezhe; Li, Duanbin; Lin, Maoning; Jiang, Hangpan; Xu, Tian; Shan, Yu; Fu, Guosheng; Wang, Min; Zhang, Wenbin (Frontiers in Physiology, 2022)
Background: The hemoglobin glycation index (HGI) quantifies the inter-individual variation in glycation and is positively associated with cardiovascular diseases. However, the association between HGI and contrast-induced acute kidney injury (CI-AKI) remains unclear. Therefore, this study aimed to assess the association of HGI with CI-AKI. Methods: In this observational study, a total of 3142 patients undergoing coronary angiography (CAG) or percutaneous coronary intervention (PCI) were included. The HGI was calculated as the difference between the measured glycated hemoglobin (HbA1c) and predicted HbA1c. CI-AKI was defined as an increase of either 25% or 0.5 mg/dL (44.2 μmol/L) in serum creatinine (SCr) level within 72 hours following the exposure to contrast medium. Piecewise linear regression analysis was conducted to testify the association of HGI with the proportion of SCr elevation. Modified poisson regression analysis was performed to determine the association between HGI and CI-AKI. Exploratory analysis was also performed according to the stratification of HbA1c levels. Results: Among 3142 patients, the average age was 66.9 years and 483(15.4%) suffered CI-AKI. Piecewise linear regression analysis demonstrated the linear association of HGI with the proportion of SCr elevation on both positive and negative sides of HGI (HGI <0: β=-9.537, 95% CI [-12.057 to -7.017], P<0.001; HGI ≥0: β=1.655, 95% CI [0.125 to 3.186], P=0.034). Modified poisson regression analysis showed that higher absolute value of HGI was strongly associated with higher incidence of CI-AKI ([<-1.0 vs. -0.2 to 0.2]: aRR=1.897, 95% CI [1.467 to 2.452], P<0.001; [≥1.0 vs. -0.2 to 0.2]: aRR=1.545, 95% CI [1.171 to 2.037], P=0.002). Furthermore, the results in exploratory analysis showed that such association still remained irrespective of HbA1c levels. Conclusions: Higher absolute value of HGI was strongly associated with higher incidence of CI-AKI in patients undergoing CAG and PCI.